The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/1754-9485.12947
|View full text |Cite
|
Sign up to set email alerts
|

Extreme hypofractionated proton radiotherapy for prostate cancer using pencil beam scanning: Dosimetry, acute toxicity and preliminary results

Abstract: Introduction Extreme hypofractionated radiotherapy for prostate cancer is a common modality in photon therapy. Pencil beam scanning (PBS) in similar fractionation allows better dose distribution and makes proton therapy more available for such patients. The purpose of this study is the feasibility of extreme proton hypofractionated radiotherapy and publication of early clinical results. Methods Two hundred patients with early‐stage prostate cancer were treated with IMPT (intensity‐modulated proton therapy), ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
1
16
1
1
Order By: Relevance
“…Using the same fractionation scheme techniques as Kole et al, Moteabbed et al [5] found that the PTV coverage (D 98 isodose) was 95%, which is similar to our results (96.79%). The mean PTV dose for IMPT in our study was 37.18 CGE, which is similar to the results observed by Kubes et al (36.71 CGE) [13]. Compared to standard fractionation, we found a lower mean PTV dose (% prescribed dose) for PS (98.27%) than Vargas et al [12] (102.4%) and for IMPT when compared to the data reported by Tran et al (102.6% vs. 104.8%) [28].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Using the same fractionation scheme techniques as Kole et al, Moteabbed et al [5] found that the PTV coverage (D 98 isodose) was 95%, which is similar to our results (96.79%). The mean PTV dose for IMPT in our study was 37.18 CGE, which is similar to the results observed by Kubes et al (36.71 CGE) [13]. Compared to standard fractionation, we found a lower mean PTV dose (% prescribed dose) for PS (98.27%) than Vargas et al [12] (102.4%) and for IMPT when compared to the data reported by Tran et al (102.6% vs. 104.8%) [28].…”
Section: Discussionsupporting
confidence: 92%
“…Unfortunately, our study design does not allow us to assess treatment-related toxicity. IMPT is generally considered to have better dose distribution than PS [13,15]. Mishra et al [17] compared PS to IMPT, finding no differences in mean quality of life scores or acute grade ≥ 2 GI toxicity at one-year, but they did observe higher rates of acute grade ≥ 2 GU toxicity in the IMPT group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the number of PBRT centers are increasing worldwide [5], additional experimental data, e.g., on combination with drugs (chemotherapy, small molecules, inhibitors), tumor microenvironment, and alternative fractionation schedules, are needed to explore the full potential of this therapy [6][7][8]. Like cancer research in general, PBRT faces the problem of defining reproducible, reliable, and practical models of tumors and normal tissues, which reflect the effects of complex treatment modalities and the heterogeneous response of patients [9].…”
Section: Introductionmentioning
confidence: 99%